Exploring the social-ecological drivers and impacts of invasive alien plant induced regime shifts in the grasslands of the Eastern Cape, South Africa - Mandlana, Qhamani (Stellenbosch : Stellenbosch University, 2023)
Thesis (MScFoodSc)--Stellenbosch University, 2023.